Mayor Jantje : Cerita tuan tanah batavia abad ke -19 / Johan Febricius; Penerjemah, Tim Masup Jakarta; Penyunting, Fadjriah Nurdiasih - FABRICIUS, Johan; TIM Masrup Jakarta (Masup, 2008)
xlii, 194 hlm. : Ilus. ; 17,5 cm.